2022
DOI: 10.3389/fphar.2022.962223
|View full text |Cite
|
Sign up to set email alerts
|

Up-and-coming anti-epileptic effect of aloesone in Aloe vera: Evidenced by integrating network pharmacological analysis, in vitro, and in vivo models

Abstract: Background:Aloe vera is a medically valuable plant with anti-epileptic activity; however, its mechanism of action remains unknown. In this study, network pharmacological, in vitro, and in vivo experiments were carried out to explore the potential anti-epileptic components and targets of Aloe vera.Methods: The main active components of Aloe vera were identified by searching the Traditional Chinese Medicine System Pharmacology database. Targets of Aloe vera were predicted using SwissTargetPrediction, whereas inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Results demonstrated that these concentrations of aloesone did not affect the survival of RAW264.7 cells ( Figure 1 A,B). According to our previous study, concentrations varying from 0.1 to 100 µM of aloesone were shown to ameliorate glutamate-induced neuron injury, and these concentrations were applied in subsequent experiments [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results demonstrated that these concentrations of aloesone did not affect the survival of RAW264.7 cells ( Figure 1 A,B). According to our previous study, concentrations varying from 0.1 to 100 µM of aloesone were shown to ameliorate glutamate-induced neuron injury, and these concentrations were applied in subsequent experiments [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, the cells were washed with PBS and stained with an FITC-conjugated secondary antibody (Boster) for 2 h at 37 °C, followed by 4′,6-diamidino-2-phenylindole (DAPI, Boster) for 5 min in the dark. A magnification microscope (Zeiss X-Cite) was used to observe the stained cells at a 200× magnification [ 24 , 57 ]. Subsequently, ImageJ software (1.52a, Wayne Rasband, Bethesda, MD, USA) was used to process the fluorescent images [ 58 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation